Visualizing G30s/PKI Tragedy Through Interactive Projector Media at Monumen Pancasila Sakti - Yiesha Tabina; Mita Purbasari Wahidiyat (ULTIMART Jurnal Komunikasi Visual, 2021)
The G30S/PKI incident is an event that continues to imprint in the hearts of all Indonesian people because it is closely related to the Lubang Buaya incident, which is located in front of the Pancasila Sakti Monument. This large building is usually visited by students just for school assignments, even though in it lies the story of the struggle of the Indonesian people against communism. The quiet and cold atmosphere inside the monument makes visitors pass through dioramas and the hallways just like that. To spread the essential historical event, we need a way to change the stereotype that museums are boring. In this study, projection mapping is used inside the Pancasila Sakti Monument to give visitors a new sensation and experience through visuals. The research method uses qualitative data collection techniques in the form of location observations, interviews with the head of the research object guidance, and several visitors. The results of this project are interactive projections in the form of moving animated visuals that can be interacted with so that visitors get a real story experience. It is hoped that with the use of interesting animation, museums in Indonesia can compete with other places visited by many young people. Keywords: visual; G30S/PKI; monument Pancasila Sakti; projection interactive; youngsters